A Manual for Law Schools on Adjunct Faculty - Karen Tokarz (Washington University Law Quarterly, 1998)
In 1991, American Bar Association (ABA) President Sandy D'Alemberte created the ABA Coordinating Committee on Legal Education with the mandate to explore ways to expand the participation of practicing lawyers and judges in American legal education. The committee, composed of representatives from a substantial number of ABA sections and a roughly equivalent number of law school professors, focused on the role of part-time and adjunct faculty in American law schools, and published in 1993 the first edition of A Manual for Law Schools on Adjunct Faculty. The purpose of this Manual is to highlight steps that law schools might take to provide adjunct faculty with orientation, guidance, monitoring, and evaluation, and in the process enrich the educational program of the school. Neither committee concludes that any of the points set forth in the Manual are in any way mandatory for any institution. The purpose of the document is not regulatory, but is altogether suggestive and hortatory. The information provided in this Manual is offered merely as a starting point for discussions regarding orientation, guidance, monitoring, evaluation, and other issues relating to adjunct faculty at individual schools.
Keywords: Law teachers; Law school faculty; Law schools; Lawyers